A novel ultra-strong hot stamping steel treated by quenching and partitioning process. Issue 18 (12th December 2018) - Liang, Jiangtao; Zhao, Zhengzhi; Sun, Binhan; Lu, Hongzhou; Liang, Juhua; He, Qing; Chen, Weijian; Tang, Di
ABSTRACT: In the present study, we design a novel hot stamping steel containing high amounts of C and Si and micro-alloying element (i.e. Nb). The steel was subjected to quenching and partitioning (Q&P) process. The new Q&P treated hot stamping steel exhibits a significantly improved mechanical property in terms of strength, ductility and impact toughness compared with the traditional 22MnB5 hot stamping steel. The influence of partitioning time on the microstructure and mechanical properties was investigated. The retained austenite (RA) fraction and the carbon content of RA significantly increased with higher partitioning times. With increasing partitioning time, the uniform elongation, total elongation, strength-ductility balance and impact energy was also remarkably enhanced. The maximum strength-ductility balance achieves around 23 GPa %.